An ultrasensitive fluorescence aptasensor for carcino-embryonic antigen detection based on fluorescence resonance energy transfer from upconversion phosphors to Au nanoparticles. Issue 13 (19th March 2018) - Li, Xiang-Hui; Sun, Wei-Ming; Wu, Juan; Gao, Yao; Chen, Jing-Hua; Chen, Min; Ou, Qi-Shui
Abstract : A FRET-based aptasensor for CEA detection was constructed by using upconversion nanoparticles as the energy donor and Au nanoparticles as the energy acceptor. Abstract : A novel fluorescence resonance energy transfer (FRET)-based aptasensor was proposed for carcino-embryonic antigen (CEA) detection utilizing NaYF4 :Yb 3+, Er 3+ upconversion nanoparticles (UCNPs) and gold nanoparticles (Au-NPs) as the energy donor and acceptor, respectively. The FRET process occurs when the single-stranded DNA modified UCNPs and Au-NPs are linked together by the CEA aptamer, which leads to the fluorescence quenching of UCNPs. However, the presence of CEA splits the above fluorescence-suppressed Au-NPs–aptamer–UCNPs sandwich complex, resulting in the fluorescence recovery of UCNPs. The recovery of fluorescence intensity is linearly correlated to the concentration of CEA in the range of 0.05–2.0 ng mL −1, enabling the detection and quantification of CEA. Such a sandwich-type FRET-based assay possesses a low limit of detection (0.02 ng mL −1 ) and satisfactory selectivity and reproducibility, indicating that this biosensor is applicable for the trace detection of the CEA protein.